Optimized cultivation of Campylobacter concisus from gut mucosal biopsies in inflammatory bowel disease. Issue 1 (December 2016) - Kirk, Karina; Nielsen, Hans; Thorlacius-Ussing, Ole; Nielsen, Henrik
Abstract Background Campylobacter concisus is a commensal of the human oral flora that has been linked to prolonged diarrhea and inflammatory bowel disease (IBD). It has been detected more often from intestinal biopsies in patients with IBD compared to healthy controls using PCR-based techniques, whereas the number ofC. concisus culture-positive biopsies in previous studies has been very limited. Determining the rate of viable isolates present in the gut mucosa is of great importance when evaluating the role in different disease presentations. We therefore investigated a novel two-step cultivation procedure combining anaerobic and microaerobic incubation from several gut mucosal sites to improve isolate yield, and compared this to PCR results, from IBD patients and healthy controls. Results Cultivation with the novel two-step procedure yielded a higher rate ofC. concisus isolates from mucosal biopsies than previously reported by other methods. From 52 IBD patients, 52/245 (21 %) biopsies were culture positive forC. concisus, while 121/245 (49 %) of biopsies were PCR positive. For 26 healthy controls, the numbers were 23/182 (13 %) and 66/182 (36 %), respectively (p < 0.001). The rate of cultivation and PCR detection was higher for IBD patients compared to healthy controls (p = 0.021, p = 0.008, respectively). Conclusions Patients with IBD had a higher prevalence ofC. concisus than healthy controls, by both cultivation and PCR detection. We found a higher rate ofC. concisus isolates from gut mucosal biopsies in both IBD patients and healthy controls than in preceding studies, indicating that colonization ofC. concisus in the gastrointestinal tract is more extensive than previously assumed.